Advances in fluorescent-image guided surgery - Landau, Mark J.; Gould, Daniel J.; Patel, Ketan M. (Annals of Translational Medicine; Vol 4, No 20 (October 31, 2016): Annals of Translational Medicine (Focus on “Innovations & Technology in Surgery”), 2016)
Fluorescence imaging is increasingly gaining intraoperative applications. Here, we highlight a few recent advances in the surgical use of fluorescent probes.